2022
DOI: 10.1590/1809-4430-eng.agric.v42n4e20220050/2022
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Controller Applied to Temperature Adjustment in Incubation of Free-Range Eggs

Abstract: Temperature variation in egg incubation can negatively affect the hatching time and weight gain of chicks, hence improving the incubator temperature accuracy can improve hatching rates. Controllers based on the fuzzy methodology have shown great potential for use in controlling incubator temperature variations. Therefore, the objective of this study is to develop and evaluate a fuzzy logic-based controller for egg incubation. Four identical incubators were configured: two with a fuzzy controller and two with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…AI holds great potential for change in the healthcare industry. Indeed, healthcare companies face unheard-of difficulties caused by aging and labor shortages, shifting demographics, administrative demands, rising morbidity, and changes in information technology need [31][32][33][34][35][36][37][38][39][40]. Utilizing AI to provide accessible healthcare solutions with successful patient outcomes [31][32][33].…”
Section: E Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI holds great potential for change in the healthcare industry. Indeed, healthcare companies face unheard-of difficulties caused by aging and labor shortages, shifting demographics, administrative demands, rising morbidity, and changes in information technology need [31][32][33][34][35][36][37][38][39][40]. Utilizing AI to provide accessible healthcare solutions with successful patient outcomes [31][32][33].…”
Section: E Discussionmentioning
confidence: 99%
“…Due to the possibility of extensive automation, this rise in AI is anticipated to have an impact on the role of healthcare professionals, particularly those working with digital data, such as radiologists or pathologists. The domination of AI in the healthcare industry is anticipated to displace individuals who do not use technology or take over some of the tasks currently performed by doctors or healthcare administrators [35][36][37]. For instance, a recent study of Korean doctors found that only 6% of the respondents thought AI could replace them, although 35% of them believing it might.…”
Section: E Discussionmentioning
confidence: 99%